Guanidine masked catechol initiator promoted ring-opening polymerization of sarcosine N-carboxyanhydride. Issue 4 (18th May 2020) - Gebru, Hailemariam; Tianfo, Guo; Li, Zhenjiang
Abstract: The synthesis of catechol polymers often demands tedious protection and deprotection steps. In this work, the role of a guanidine base to subdue the catechol functions and promote the ring-opening polymerization (ROP) is suggested. Accordingly, guanidine, 7-methyl-1, 5, 7-triazabicyclo[4.4.0]dec-5-ene (MTBD), was employed to mediate ROP of N -carboxyanhydride (NCA) from a catechol initiator. MTBD played a dual-role in ROP of sarcosine-NCA (Sar-NCA) and masking the catechol initiator concurrently. Catechol-ended polysarcosine (PSar) was synthesized with a predicted molecular weight ( M n, SEC = 3.5 kg mol −1, M n, NMR = 3.7 kg mol −1 ) and narrow dispersities ( Đ < 1.11). This one base two-function strategy showed a new path for the synthesis of catechol functionalized polymers. Graphical Abstract: